FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KESERTAAN KB KELUARGA MISKIN PENGGUNA JAMKESMAS / PKH DI KABUPATEN CIREBON 2010 - Chotimah, Indira (HEARTY, 2013)
Family planning participation is an instrument to halt population growth rate and to maintain family welfare in developing countries like Indonesia. Indonesia has vast population mostly poor that vulnerable to be short of an access to the health service such as family planning.A quantitative study was carried out using cross sectional design. Secondary data was collected from Studi Maternal PPK UI and in depth interview was also conducted. This study is aimed to identify the factors such as socio demography, socio psychology, and service provider that related to the family planning participation.Bivariate analysis resulted that factors had significant relation were parity, tribe, age, age at the first time got pregnant, and type of assurance owned. In depth interview result showed that the reason of respondents did not participate in family planning because they were afraid of the side effects from using contraception.The high coverage of family planning participation in districts that have high coverage of family planning because of counseling effort that given after delivery towards PUS, availability of contraception in an adequate amount in each public health center and village midwife, coordination among midwife coordinator and village midwife, public health center Health Office as well as National Family Planning Coordinating Agency (BKKBN).It is suggested that government should implement PKH program besides Jamkesmas Program in another area, particularly in the high poverty rate area due to both assurances are not only giving contraception for free but also access to the health service.